PENGARUH MODAL KERJA, LIKUIDITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN SUB SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2023 - Yanti, Anggi Putri Dwi; Pramitasari, Triska Dewi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of working capital, liquidity, and leverage on firm value with profitability as a moderating variable in energy sub-sector companies listed on the IDX for the 2019-2023 period. The sample used in this study is 6 energy sub-sector companies listed on the Indonesia Stock Exchange during the 5 years with sampling using a purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of direct influence hypothesis testing using the Smart PLS 3.0 application show that working capital has a positive but insignificant effect on firm value, liquidity has a negative but significant effect on firm value, leverage has a negative but significant effect on firm value, profitability positively and insignificantly moderates the effect of liquidity on firm value.